Baicalin relieves complement alternative pathway activation-induced lung inflammation through inhibition of NF-κB pathway - Jiao Li; Qi-Yun Zhang; Qing-Yu Lu; Qiao-Zhou Liu; Li Guo; Min Li; Qian-Yun Sun (BMC Complementary Medicine and Therapies, 2024)
Abstract Introduction Acute lung injury (ALI) as one kind of acute pulmonary inflammatory disorder, manifests primarily as damage to alveolar epithelial cells and microvascular endothelial cells. Activation of the complement system is a common pathological mechanism in ALI induced by diverse factors, with the complement alternative pathway assuming a pivotal role. Baicalin, a flavonoid derived from the root of Scutellaria baicalensis Georgi, exhibits noteworthy biological activities. The present study attempted the interventional effects and underlying mechanisms of baicalin in microangiopathy in ALI induced by complement alternative pathway activation. Methods Activation of the complement alternative pathway by cobra venom factor (CVF). HMEC cells were pretreated with baicalin and then exposed to complement activation products. The expression of inflammatory mediators was detected by ELISA, and the intranuclear transcriptional activity of NF-κB was assessed by a dual fluorescent kinase reporter gene assay kit. Before establishing the ALI mouse model, baicalin or PDTC was gavaged for 7 d. CVF was injected into the tail vein to establish the ALI model. The levels of inflammatory mediators in BALF and serum were determined by ELISA. HE staining and immunohistochemistry evaluated pathological changes, complement activation product deposition, and NF-κB p65 phosphorylation in lung tissue. Results Baicalin reduced complement alternative activation product-induced expression of HMEC cells adhesion molecules (ICAM-1, VCAM-1, E-selectin) and cytokines (IL-6, TNF-α) as well as upregulation of NF-κB intranuclear transcriptional activity. Baicalin intervention reduced the number of inflammatory cells and protein content in the BALF and decreased the levels of IL-6, TNF-α, and ICAM-1 in serum and IL-6, TNF-α, ICAM-1, and P-selectin in BLAF. In addition, baicalin attenuated inflammatory cell infiltration in the lung of ALI mice and reduced the deposition of complement activation products (C5a, C5b-9) and phosphorylation of NF-κB p65 in lung tissue. Conclusion Baicalin relieves complement alternative pathway activation-induced lung inflammation by inhibition of NF-κB pathway, delaying the progression of ALI.